Refleksi Kritis atas Kitab Mazmur 1:1–6 “Jalan Orang Benar dan Jalan Orang Fasik” - Nikodemus Nikodemus; Andreas Jimmy (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This paper focuses on a critical reflection on the text of Psalm 1:1-6, specifically introducing two opposing paths between "the way of the righteous" and "the way of the wicked." A critical approach to this text is carried out by considering interpretive and contextual aspects, and finding the meanings contained therein by connecting the experiences of modern-millennial humans. This writing uses qualitative methods and a library research approach, to the Bible, and the book of Psalms 1-72, as well as the book Traces of God's Salvation Work: An Introduction and the Ins and Outs of the Old Testament Scriptures. This writing involves critical reflection on the structure of the text, key words, and moral messages hidden in Psalm 1:1-6. In addition, this paper also explores the social and spiritual implications of understanding "the way of the righteous" and "the way of the wicked" in the context of modern-millennial society. The main finding in this writing is to provide deeper insight into how the concepts expressed in the Book of Psalms 1:1-6 can be applied in the lives of modern-millennial humans, as well as how the moral messages from the text can be relevant in guiding individuals in choosing the right path in life.